Theoretical Study on the Reinforcement Capacity of Cable Nets in Active Rockfall Protection System - CUI, Lianming; WANG, Min; SUN, Jianhu; CHU, Zhaojun (Engineering Transactions, 2017)
Active rockfall protection system is a pattern-anchored yet flexible cable net system. It consists of cable net panels and longitudinal and horizontal support cables. The panels support loads developed from unstable rock and transmit this load to the longitudinal and horizontal support cables. In the corner of each panel is an anchor that takes the load from support cables and transmits it into the stable rock. The calculation method is developed to study the reinforcement capacity of cable nets used in the protection system. The formula to calculate the reinforcement force of the cable nets with the concentrated load has been obtained and the results are compared with the experimental results. The theoretical research provides useful results for cable nets used in the active rockfall protection system.